Pengaruh Kualitas Pelayanan dan Promosi Digital terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah pada Generasi Milenial PT. Pegadaian Cabang Kampung Lalang Kota Medan - Anggi Randy Syahputra; Adelina Lubis; Minda Muliana Br Sebayang (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze the effects of Service Quality and Digital Promotion on Customer Loyalty through Customer Satisfaction as an intervening variable among millennial customers using the services of PT Pegadaian, Kampung Lalang Branch, Medan City. This study employed a quantitative approach involving 93 respondents. The data were analyzed using Partial Least Squares (PLS) with SmartPLS 4.0. The results indicate that Service Quality has a positive and significant effect on Customer Satisfaction (T-Statistics = 3.732 > 1.96; P-Values = 0.000) and Customer Loyalty (T-Statistics = 3.559 > 1.96; P-Values = 0.006). Digital Promotion also has a positive and significant effect on Customer Satisfaction (T-Statistics = 4.941 > 1.96; P-Values = 0.000) and Customer Loyalty (T-Statistics = 3.247 > 1.96; P-Values = 0.001). Furthermore, Customer Satisfaction has a positive and significant effect on Customer Loyalty (T-Statistics = 1.972 > 1.96; P-Values = 0.049). The mediation analysis demonstrates that Customer Satisfaction significantly mediates the effects of Service Quality and Digital Promotion on Customer Loyalty. These findings confirm that improving service quality and implementing effective digital promotion strategies can enhance customer satisfaction and loyalty, particularly among millennials. Therefore, PT Pegadaian is advised to continuously improve its digital-based services and strengthen its digital marketing communication strategies to maintain customer loyalty in the era of digital transformation.